A IMPLEMENTASI PROGRAM EKSTRAKULIKULER BELAJAR BAHASA ARAB DI SMPIT SUBULUSSALAM DI DESA RATNA DAYA, RAMAN UTARA, LAMPUNG TIMUR - Dinarudin; Mujahada, Kharis Syuhud (POACE: Jurnal Program Studi Adminitrasi Pendidikan, 2025)
This research is motivated by the importance of Arabic language mastery as a unifying language for Muslims and a tool for deepening religious knowledge. The study aims to describe the implementation of the Arabic language extracurricular program and analyze the improvement of students' mahārāh al-kalām at SMPIT SUBULUSSALAM, Ratna Daya Village, North Raman, East Lampung. Using a qualitative approach, data were collected through passive participation observation, guided free interviews with the supervising teacher and six students, and documentation. Data analysis techniques followed Miles and Huberman's interactive model with triangulation of sources, theories, and methods for data validity. The results showed that the Arabic language extracurricular program was conducted every afternoon with 22 participants from grades VII to IX. Learning strategies included daily conversations, vocabulary application in daily conversation, writing new vocabulary, and practicing Arabic speeches. Evaluation was carried out at the end of each meeting and semester through written, oral, and practical tests. There was a significant improvement in students' mahārāh al-kalām, reflected in increased Arabic subject report card scores and communication skills. It was concluded that the implementation of the Arabic language extracurricular program effectively improved students' Arabic speaking skills at SMPIT SUBULUSSALAM.